2015
DOI: 10.1021/acs.est.5b03868
|View full text |Cite
|
Sign up to set email alerts
|

Limitation of the Use of the Absorption Angstrom Exponent for Source Apportionment of Equivalent Black Carbon: a Case Study from the North West Indo-Gangetic Plain

Abstract: Angstrom exponent measurements of equivalent black carbon (BCeq) have recently been introduced as a novel tool to apportion the contribution of biomass burning sources to the BCeq mass. The BCeq is the mass of ideal BC with defined optical properties that, upon deposition on the aethalometer filter tape, would cause equal optical attenuation of light to the actual PM2.5 aerosol deposited. The BCeq mass hence is identical to the mass of the total light-absorbing carbon deposited on the filter tape. Here, we use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 80 publications
3
52
0
Order By: Relevance
“…A near-UV over-or underestimation of the data will substantially affect brown carbon calculations if apportionment algorithms based on the wavelength dependence of absorption are used. More details on the effects of inaccurate å ABS on the BrC / BC apportionment are discussed in Garg et al (2016), Schuster et al (2016a, b), Wang et al (2016), and references therein. A BrC estimation is beyond the scope of this paper.…”
Section: Overestimation Of Near-uv Absorption By Ae Correctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A near-UV over-or underestimation of the data will substantially affect brown carbon calculations if apportionment algorithms based on the wavelength dependence of absorption are used. More details on the effects of inaccurate å ABS on the BrC / BC apportionment are discussed in Garg et al (2016), Schuster et al (2016a, b), Wang et al (2016), and references therein. A BrC estimation is beyond the scope of this paper.…”
Section: Overestimation Of Near-uv Absorption By Ae Correctionsmentioning
confidence: 99%
“…Assuming a fixed spectral dependence of 1 for BC, several studies have estimated the BrC contribution as a function of å ABS (Favez et al, 2010;Sandradewi et al, 2008). However, given the uncertainties associated with the å ABS of BC, these methods could potentially provide erroneous BrC estimations (Garg et al, 2016;Schuster et al, 2016a, b;Wang et al, 2016).…”
mentioning
confidence: 99%
“…On the other hand, recently published studies claim that the aerosol spectral dependence is more affected by combustion conditions than the type of fuel being combusted (Garg et al, 2016;Martinsson et al, 2015). Garg et al (2016) found that the gaseous tracer for biomass burning, acetonitrile, correlated well with AAE during smoldering combustion but poorly during flaming combustion, and further that AAE varied greatly throughout combustion of the same fuel type. Calvo et al (2015) measured levoglucosan in a wood stove with controlled combustion and a traditional fireplace; they found elevated concentrations of levoglucosan during the fuel addition followed by a rapid de-crease in concentration in the flaming phase.…”
mentioning
confidence: 99%
“…Some studies have found good correlation between levoglucosan and AAE, or calculated BC from wood burning (BC WB ), using the Aethalometer model (Fuller et al, 2014;Herich et al, 2011;Lack et al, 2013). On the other hand, recently published studies claim that the aerosol spectral dependence is more affected by combustion conditions than the type of fuel being combusted (Garg et al, 2016;Martinsson et al, 2015). Garg et al (2016) found that the gaseous tracer for biomass burning, acetonitrile, correlated well with AAE during smoldering combustion but poorly during flaming combustion, and further that AAE varied greatly throughout combustion of the same fuel type.…”
mentioning
confidence: 99%
“…Several studies have used the absorption spectral dependence to apportion the fossil fuel and BB contributions to total absorption (Favez et al, 2010;Massabò et al, 2015;Sandradewi et al, 2008). However, the å abs values do not always reflect the combustion type and using it as a source apportionment parameter could lead to erroneous results (Garg et al, 2016;Lewis et al, 2008;Wang et al, 2016b).…”
mentioning
confidence: 99%